Implications of improved diagnostic imaging of small nodal metastases in head and neck cancer: Radiotherapy target volume transformation and dose de-escalation. Issue 3 (September 2018) - van den Bosch, Sven; Vogel, Wouter V.; Raaijmakers, Cornelis P.; Dijkema, Tim; Terhaard, Chris H.J.; Al-Mamgani, Abrahim; Kaanders, Johannes H.A.M.
Abstract: Diagnostic imaging continues to evolve, and now has unprecedented accuracy for detecting small nodal metastasis. This influences the tumor load in elective target volumes and subsequently has consequences for the radiotherapy dose required to control disease in these volumes. Small metastases that used to remain subclinical and were included in elective volumes, will nowadays be detected and included in high-dose volumes. Consequentially, high-dose volumes will more often contain low-volume disease. These target volume transformations lead to changes in the tumor burden in elective and "gross" tumor volumes with implications for the radiotherapy dose prescribed to these volumes. For head and neck tumors, nodal staging has evolved from mere palpation to combinations of high-resolution imaging modalities. A traditional nodal gross tumor volume in the neck typically had a minimum diameter of 10–15 mm, while nowadays much smaller tumor deposits are detected in lymph nodes. However, the current dose levels for elective nodal irradiation were empirically determined in the 1950s, and have not changed since. In this report the radiobiological consequences of target volume transformation caused by modern imaging of the neck are evaluated, and theoretically derived reductions of dose in radiotherapy for head and neck cancer are proposed. The concept of target volume transformation and subsequent strategies for dose adaptation applies to many other tumor types as well. Awareness of this concept may result in new strategies for target definition and selection of dose levels with the aim to provide optimal tumor control with less toxicity.